1999
DOI: 10.1002/(sici)1097-4636(199907)46:1<112::aid-jbm13>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of morphology in UHMWPE following accelerated aging: The effect of heating rates

Abstract: Accelerated aging methods are used to evaluate the oxidative stability of UHMWPE components for total joint replacements. In this study, we traced the evolution of the crystalline morphology during accelerated thermal aging of UHMWPE in air with the intent of explaining previous, counterintuitive heating rate effects. GUR4150HP extruded rod stock material was machined into miniature (0.5 mm thick) specimens that were either gamma irradiated in air or in nitrogen (27 +/- 3 kGy) or left unirradiated (control). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Several studies have reported an increase in PE crystallinity upon ageing, and this behaviour has been related to a rearrangement of the polymeric chains as a result of their increased mobility due to thermal ageing . However, for EtO‐sterilized samples, this effect appeared less pronounced; on the other hand, thermally unstabilized XLPE samples submitted to accelerated ageing did not display any increase in crystallinity, as well as XLPE and UHMWPE components after 2 years of real‐time shelf ageing .…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported an increase in PE crystallinity upon ageing, and this behaviour has been related to a rearrangement of the polymeric chains as a result of their increased mobility due to thermal ageing . However, for EtO‐sterilized samples, this effect appeared less pronounced; on the other hand, thermally unstabilized XLPE samples submitted to accelerated ageing did not display any increase in crystallinity, as well as XLPE and UHMWPE components after 2 years of real‐time shelf ageing .…”
Section: Discussionmentioning
confidence: 94%
“…Also, the aging of polymer that performed at 80°C for 23 days has found to be equivalent to approximately 8 years shelf aging 1. Meanwhile, many researchers have highlighted certain limitations of accelerated thermal aging techniques 18, 19. For example, thermal aging of UHMWPE is considered as a severe oxidative process compared to natural aging.…”
Section: Introductionmentioning
confidence: 99%
“…The chain scission that occurs during aging of UHMWPE leads to shorter molecules with higher mobility. Thus they can pack more efficiently into the lamellae leading to an increase in overall crystallinity and density (Kurtz [1999b]). The chain scission also affects the tie molecules by decreasing the effectiveness in supporting load leading to the breakage of the polymer long chains, reducing the molecular weight, increasing the brittleness, and weakening the properties of aged UHMWPE (Fouad [2010]).…”
Section: Ageing Of Uhmwpe and Uhmwpe-cnt Nanocompositesmentioning
confidence: 99%